PENGARUH PROMOSI DAN STORE ATMOSPHERE TERHADAP IMPULSE BUYING DENGAN SHOPPING EMOTION SEBAGAI VARIABEL INTERVENING PADA DEPARTEMENT STORE MIROTA KAMPUS YOGYAKARTA: PENGARUH PROMOSI DAN STORE ATMOSPHERE TERHADAP IMPULSE BUYING DENGAN SHOPPING EMOTION SEBAGAI VARIABEL INTERVENING PADA DEPARTEMENT STORE MIROTA KAMPUS YOGYAKARTA - Kania Indraswari, Dara (ECO-BUILD, 2025)
This study aimed to analyze the effect of promotions and store atmosphere against impulse buying either directly or through an intervening variable that is shopping emotion. The object of this research is the department store Mirota Campus Yogyakarta. This study using purposive sampling method. The samples used were 100 samples. The type of data in this research is the primary data where the data was obtained directly from the source using a questionnaire as an instrument in the study. This study uses SPSS with path analysis as a research model. The results showed that the store atmosphere affect consumers in making impulse buying either directly or through an intervening variable. While the promotion does not significantly influence consumer behavior in doing impulse buying. Shopping emotion as an intervening variable mediating variables only store atmosphere while the promotion is not.